Information modelling and knowledge bases XXVI - Thalheim, B. (Bernhard), 1952- (Frontiers in artificial intelligence and applications ;, 2014)
Within the last three decades, information modelling and knowledge bases have become essential subjects, not only for academic communities related to information systems and computer science, but also for businesses where information technology is applied. This book presents the proceedings of EJC 2014, the 24th International Conference on Information Modelling and Knowledge Bases, held in Kiel, Germany, in June 2014. The main themes of the conference were: conceptual modelling, including modelling and specification languages, domain specific conceptual modelling, and validating and communicat.